Developmental trajectories of firearm carrying among Justice-involved youth: effects of socioeconomic status and gang membership - Wojciechowski, Thomas (Criminal justice studies, 2023)
There is limited understanding of how socioeconomic status, gang membership, and their interaction predicts the development of firearm carrying. The Pathways to Desistance data were analyzed. Group-based trajectory modeling identified heterogeneity in patterns of firearm carrying. Multinomial logistic regression examined socioeconomic status and gang membership as predictive of development. A seven-group firearm carrying model best fit the data. Gang membership predicted increased risk of assignment to the Low Chronic, Adolescence Limited, and High Chronic groups. Socioeconomic status did not exert a significant direct effect on group assignment. The interaction between socioeconomic status and gang membership was significant and negative for the High Chronic group. Gang members with higher socioeconomic status presented the highest risk of high chronic firearm carrying.